THE EFFECTS OF SALES GROWTH AND TOTAL ASSETS TURN OVER ON COMPANY VALUE WITH PROFITABILITY AND DEBT POLICY AS MEDIATION VARIABLES (CASE STUDY ON TRANSPORTATION COMPANY LISTED ON THE IDX FOR 2015-2018 PERIOD) - Andriani, Vera; Haryetti, Haryetti; Fathoni, Ahmad Fauzan; Paramitha, Anggia (International Journal of Economic, Business & Applications, 2021)
This study aims to test and seek empirical evidence of the factors that influence company value. The factors tested in this study include Sales Growth and Total Asset Turn Over. Researcher adds Profitability and Debt Policy as mediating variables in this study. The population of this research is transportation companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The research sample was selected using purposive sampling criteria so that 25 transportation companies were selected that were listed consecutively on the Indonesia Stock Exchange starting from the 2015-2018 period. To examine the factors that contribute to company value, this study uses path analysis and uses SPSS Statistics version 23 as an analysis tool. The results of this study indicate that Sales Growth and Total Asset Turn Over have a significant effect on Profitability, Sales Growth and Total Asset Turn Over have a significant effect on Debt Policy, Total Asset Turn Over and Debt Policies have a significant effect on Company Value. Meanwhile, Sales Growth and Profitability have no significant effect on Company Value. Debt policy as a mediating variable is able to mediate the effect of the dependent variable on the independent variable in this study. Meanwhile, Profitability as a mediating variable is not able to mediate the effect of the dependent variable on the independent variable in this study.